1998
DOI: 10.4269/ajtmh.1998.59.35
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the incidence of infection with Plasmodium falciparum among international travelers.

Abstract: Abstract. Circumsporozoite (CS) antibodies, indicating plasmodial infection but not necessarily development of disease, have been shown to be reliable indicators of transmission in endemic areas. To estimate the actual rate of plasmodial infection, the prevalence of CS antibodies was investigated by an ELISA test system in a selected population of 2,131 travelers returning from areas endemic for malaria who presented to an outpatient clinic without any apparent symptom or clinical sign of malaria. Serum specim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
16
0
4

Year Published

1999
1999
2008
2008

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 35 publications
(22 citation statements)
references
References 13 publications
2
16
0
4
Order By: Relevance
“…*Categories of maleria risk are defined based on world regions and country-specific risk levels. 2,7,8,21,94 †The CDC currently does not recommend SBET alone or seasonal chemoprophylaxis for any malarious areas. ‡Rapid diagnostic tests for malaria could become an attractive option in occasional circumstances if technical problems are overcome.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…*Categories of maleria risk are defined based on world regions and country-specific risk levels. 2,7,8,21,94 †The CDC currently does not recommend SBET alone or seasonal chemoprophylaxis for any malarious areas. ‡Rapid diagnostic tests for malaria could become an attractive option in occasional circumstances if technical problems are overcome.…”
Section: Discussionmentioning
confidence: 99%
“…6 Investigators using Plasmodium falciparum circumsporozoite antibody titers as a measure of malaria exposure found large variation in the proportion of seropositive travelers depending on the area visited: West Africa (22.2%), East Africa (21.8%), and southern Africa (15.4%), in contrast to Central America (4.2%), Southeast Asia (3.4%), East Asia (3.3%), South America (2.4%), and the Indian subcontinent (2.2%). 7 Recent analyses of traveler databases have found the highest risk of acquiring malaria in Africa and Oceania, an intermediate risk in South Asia, and a lower risk in Central America, Southeast Asia, and South America. 2,8 Long-term travelers, particularly occupational travelers such as miners, are at an even higher risk.…”
Section: Risk Of Malaria In Long-term Travelersmentioning
confidence: 99%
“…Consequently, exclusion of potentially infected donors is widely used to prevent transfusion transmitted malaria (Reesink 2005). Previous reports suggested that a malaria antibody test is effective in detecting malaria infection in travelers returning from overseas (Knappik et al 2002) and in non-immune visitors to endemic areas after their departure (Jelinek et al 1998, Knappik et al 2002.…”
mentioning
confidence: 99%
“…Daß solche Annahmen aufgrund des völlig anderen Risikoverhaltens von Reisenden und Einheimischen in Endemiegebieten naturgemäß nur ungenaue Näherungen sein konnten, wurde mangels besserer methodischer Möglichkeiten akzeptiert. Weltweit das höchste Malariarisiko wird für Westafrika südlich der Sahara angenommen (ca 2% aller ungeschützten Reisenden), gefolgt vom wesentlich häu-figer besuchten Ostafrika [8]. Dementsprechend werden für Reisen in diese Gegenden strikte Expositionsprophylaxe und die zusätzliche Einnahme wirksamer Chemoprophylaktika empfohlen [3,13].…”
Section: Risikoabschätzungunclassified
“…Auch bei Nichtimmunen konnte gezeigt werden, daß das Transmissionsrisiko durch den Nachweis von CSP-Antikörpern geographisch unterschiedlich quantifizierbar ist [6,7,8,10]. Dabei kann eine stattgefundene Malariainfektion auch ohne anschließenden Ausbruch der Erkrankung, z.B.…”
Section: Risikoabschätzungunclassified